Monitoring and Evaluation of Teacher Performance Improvement - Widja Hadi (Journal of Contemporary Islamic Primary Education, 2023)
This research aims to describe monitoring and evaluation of improving teacher performance in LC Laesansi (Mindanao-Philippines). This research uses a qualitative approach with descriptive study methods. Based on the research results, it was found that: First, management planning to improve teacher performance, namely, program personnel discuss determining the program and steps that must be taken by involving teachers in various education and training, activating teacher forums in the field of study, providing the necessary facilities and carrying out supervision pushing / directing. The efforts made by the school principal turned out to be effective. Second, monitoring and evaluation of teacher performance improvement management has been carried out by the school principal and an appointed team with the aim of finding out any deficiencies in implementation so that improvements can be made to plans that will be prepared and implemented next. Third, the problems found in teacher performance improvement management include external problems